2016
DOI: 10.1051/matecconf/20168101007
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Safety Transport Framework for Schools: A Review of Route Planning and Tracking Systems

Abstract: Abstract. This work presents a review of recent literature in intelligent school transportation frameworks, particularly focusing on route planning, real time vehicle and children tracking. The focus on route planning and tracking is to identify the hidden practical problems and threats present in school transportation, bearing in mind safety. Different methods and technologies used for route planning and vehicle as well as children tracking are reviewed. A discussion is provided on the current frameworks alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Por otro lado, Ramachandran, Sahandi, Prakoonwit, y Khan (2016), realizan una revisión de la literatura en cuanto a transporte escolar inteligente, centrándose en la planificación de rutas, vehículos en tiempo real y seguimiento de niños. El enfoque en la planificación y seguimiento de rutas es identificar los problemas prácticos ocultos y las amenazas presentes en el transporte escolar, teniendo en cuenta la seguridad.…”
Section: Estado Del Arteunclassified
“…Por otro lado, Ramachandran, Sahandi, Prakoonwit, y Khan (2016), realizan una revisión de la literatura en cuanto a transporte escolar inteligente, centrándose en la planificación de rutas, vehículos en tiempo real y seguimiento de niños. El enfoque en la planificación y seguimiento de rutas es identificar los problemas prácticos ocultos y las amenazas presentes en el transporte escolar, teniendo en cuenta la seguridad.…”
Section: Estado Del Arteunclassified
“…This concern is even more important in school transport, which is more critical than other types of transport, as it involves school children, who are the most vulnerable users. Recent advances in school transport systems has given birth to intelligent school transport systems (ISTS) which attempts to tackle issues faced in school transport which may be classified in to three major categories; school bus routing, vehicle & driver monitoring and children monitoring [13]. However, there are limited studies addressing the validation of coach operator compliance [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is still a knowledge gap with schools in respect of the operators' safety compliance which can be used prior to booking a coach. There is no specific safety model available to guide and ensure the safety of children travelling in coaches in the UK [13]. Therefore, a novel safety transport model which validates the coach operators and guides the schools to select the safest operator while booking the journey is proposed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This raises the question whether school transport through coaches in the UK is really safe? In a survey conducted in the Luton Borough Council in the UK, it was found that coaches are booked for trips based on trust of Coach Operators and schools rarely check the operators for their compliance with the safety regulations [9]. A safety transport model for schools which provides safety scores for validation of coach operators in the UK has been developed [10].…”
Section: Introductionmentioning
confidence: 99%